The acceptance of online social networks as a technology-based education tools among higher institutes students: A structural equation modeling approach - Al-Sharafi, Mohammed A.; Mufadhal, Mokhtar Esmail; Noor Azida, Sahabudin; Ruzaini, Abdullah Arshah (Sharif University of Technology, Tehran, I.R. Iran, 2019)
Educational institutes are adopting Online Social Networks (OSNs) to facilitate learning activities in university campuses. However, before implementation a new technology there is need to identify and measure the factors that influence users' acceptance of the new technology. This will aid to critically predict the success or failure of the new technology that is to be adopted. Therefore, this study aims to identify the factors that influence student’s acceptance of online social networks as learning tool. Besides, a research model is developed based on the identified factors grounded on Technology Acceptance Model (TAM). In addition, Structural Equation Model (SEM) was employed to validate the developed model hypotheses based data collected by employing online survey from 537 students in University Malaysia Pahang (UMP). Furthermore, findings from this study have significant implications and considerable value for higher educational institutes to devise better strategies for adoption of OSNs' as a learning tool.